Construção do CAPS infantojuvenil II no município de Bauru: articulações com o território - de Araújo, Deborah Placeres (2024)
In the last decade, the national literature and the technical references available on the work in the Psychosocial Care Network have shown that, in addition to the creation of the service, the implementation of the integrated care model recommended by public health policies faces numerous theoretical and practical contradictions. In this sense, the question was how a children's and youth Psychosocial Care Center (CAPSij), located in the municipality of Bauru could be organized. The methodological support of the study is based on historical and dialectical materialism. The choice of method followed scientific criteria, combined with a critical position on capitalist society and its expressions. To fully record a proposal for action in the aforementioned Unit, it was proposed to develop theoretical-conceptual research that used the available technical-scientific accumulation as its main source. Based on a review of the national literature on the subject, published in the last 10 years, the documentary survey on the trajectory of the CAPS. Based on the theory of social determination of the health-disease process, we sought to fully understand the functions of the service, highlighting the potential, limitations and challenges that constitute the struggle to build the SUS.